Injected mass deposition thresholds for lithium granule instigated triggering of edge localized modes on EAST. (16th January 2018) - Lunsford, R.; Sun, Z.; Maingi, R.; Hu, J.S.; Mansfield, D.; Xu, W.; Zuo, G.Z.; Diallo, A.; Osborne, T.; Tritz, K.; Canik, J.; Huang, M.; et al.
Abstract: The ability of an injected lithium granule to promptly trigger an edge localized mode (ELM) has been established in multiple experiments. By horizontally injecting granules ranging in diameter from 200 microns to 1 mm in diameter into the low field side of EAST H-mode discharges we have determined that granules with diameter >600 microns are successful in triggering ELMs more than 95% of the time. It was also demonstrated that below 600 microns the triggering efficiency decreased roughly with granule size. Granules were radially injected from the outer midplane with velocities 80 m s −1 into EAST upper single null discharges with an ITER like tungsten monoblock divertor. These granules were individually tracked throughout their injection cycle in order to determine their efficacy at triggering an ELM. For those granules of sufficient size, ELM triggering was a prompt response to granule injection. By simulating the granule injection with an experimentally benchmarked neutral gas shielding (NGS) model, the ablatant mass deposition required to promptly trigger an ELM is calculated and the fractional mass deposition is determined.